Contact Improvisation as a Force for Expressive Reciprocity With Young Children Who Don’t Speak (LEARNing Landscapes, 2022)
Movement can be a powerful force for sensory connection and expression in young children who sometimes don’t speak. Their kinaesthetic curiosity naturally experiments with—and forms spontaneous relationships through—touching, sensing, and moving-with the world around them. This article wonders what might happen if children’s connective movements are invited through the speculative method of contact improvisation, not as an alternative to speech or way of interpreting meaning, but simply as a space for the transmission of forces, sensations, intimacy, and reciprocity. I consider what these shared forces or sensations of expression are that generate intimacy, joy, and reciprocity beyond words.
Keywords: contact improvisation; sensation; reciprocity; posthuman; early years